Analyzing social experiments as implemented: Evidence from the HighScope Perry Preschool Program - James Heckman; Seong Hyeok Moon; Rodrigo Pinto; Peter Savelyev; Adam Yavitz (Centre for Microdata Methods and Practice (cemmap), 2010)
Social experiments are powerful sources of information about the effectiveness of interventions. In practice, initial randomization plans are almost always compromised. Multiple hypotheses are frequently tested. Significant effects are often reported with p-values that do not account for preliminary screening from a large candidate pool of possible effects. This paper develops tools for analyzing data from experiments as they are actually implemented. We apply these tools to analyze the influential HighScope Perry Preschool Program. The Perry program was a social experiment that provided preschool education and home visits to disadvantaged children during their preschool years. It was evaluated by the method of random assignment. Both treatments and controls have been followed from page 3 through page 40. Previous analyses of the Perry data assume that the planned randomization protocol was implemented. In fact, as in many social experiments, the intended randomization protocol was compromised. Accounting for compromised randomization, multiple-hypothesis testing, and small sample sizes, we find statistically significant and economically important program effects for both males and females. We also examine the representativeness of the Perry study.
Keywords: I21; C93; J15; V16; 330; early childhood intervention; compromised randomization; social experiment multiple-hypothesis testing; Gesellschaft; Sozialer Indikator; Test; Wissenschaftliche Methode; Informationsversorgung; Sozialpolitik; Bildungswesen; USA